2017
DOI: 10.1038/s41598-017-02846-2
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Superplasticity in an Ultrafine-Grained Magnesium Alloy

Abstract: Superplasticity, a phenomenon of high tensile elongation in polycrystalline materials, is highly effective in fabrication of complex parts by metal forming without any machining. Superplasticity typically occurs only at elevated homologous temperatures, where thermally-activated deformation mechanisms dominate. Here, we report the first observation of room-temperature superplasticity in a magnesium alloy, which challenges the commonly-held view of the poor room-temperature plasticity of magnesium alloys. An ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 30 publications
(53 reference statements)
1
70
0
1
Order By: Relevance
“…74,75) Moreover, Ultra-SPD enhanced the segregation of Li and Zn in the Mg/Mg and Al/Al grain boundaries, respectively. 74,75) Such microstructural modifications resulted in achieving room-temperature superplasticity in the MgLi and AlZn alloys, as shown in Figs. 11(a) and (b), respectively.…”
Section: Room-temperature Superplasticitymentioning
confidence: 97%
See 2 more Smart Citations
“…74,75) Moreover, Ultra-SPD enhanced the segregation of Li and Zn in the Mg/Mg and Al/Al grain boundaries, respectively. 74,75) Such microstructural modifications resulted in achieving room-temperature superplasticity in the MgLi and AlZn alloys, as shown in Figs. 11(a) and (b), respectively.…”
Section: Room-temperature Superplasticitymentioning
confidence: 97%
“…73) We showed recently that ultra-SPD can be employed to design new superplastic materials by engineering the chemistry and diffusivity of grain boundaries. 74,75) The application of ultra-SPD by 200 HPT turns to MgLi and AlZn alloys resulted in increasing the fraction of Mg/Li and Al/Zn interphase boundaries with high grain boundary diffusion and mobility. 74,75) Moreover, Ultra-SPD enhanced the segregation of Li and Zn in the Mg/Mg and Al/Al grain boundaries, respectively.…”
Section: Room-temperature Superplasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on model alloys of the Al–Zn and Mg–Li systems showed that formation of the UFG structure—with grain boundaries that contain layers formed by segregations of alloying elements—could ensure signs of SP in these alloys, even at room temperature (RT) . In ref., it is reported that a Al–30Zn alloy in the UFG state demonstrated elongations of 235% at RT and 265% at 100 °C, at a strain rate of 10 −4 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have shown that some materials exhibit superplastic behavior even at room temperature (RT) if grain sizes are decreased down to sub-micron levels [3 -19]. Although RT superplasticity was reported in some Sn-Bi [3], Pb-Tl [4], Pb-Sn [5] and Mg alloys [6], binary Zn-Al alloy system is one of the well-known and most commonly studied one for this purpose [7 -19]. In this alloy system, RT superplasticity was achieved in dilute Zn-Al alloys [7 -9], eutectic Zn-5Al [10] alloy and eutectoid Zn-22Al [11 -19] alloy.…”
Section: Introductionmentioning
confidence: 99%